Endotoxin and cytokines increase hepatic messenger RNA levels and serum concentrations of apolipoprotein J (clusterin) in Syrian hamsters. - Hardardóttir, I (1994)
Infection and inflammation induce alterations in hepatic synthesis and plasma concentrations of the acute phase proteins. Our results show that apolipoprotein (apo) J is a positive acute phase protein. Endotoxin (LPS), tumor necrosis factor (TNF), and interleukin (IL)-1 increased hepatic mRNA and serum protein levels of apo J in Syrian hamsters. Hepatic apo J mRNA levels increased 10- to 15-fold with doses of LPS from 0.1 to 100 micrograms/100 g body weight within 4 h and were elevated for > or = 24 h. Serum apo J concentrations were significantly increased by 16 h and further elevated to 3.3 times that of control, 24 h after LPS administration. Serum apo J was associated with high density lipoprotein and increased fivefold in this fraction, after LPS administration. Hepatic apo J mRNA levels increased 3.5- and 4.6-fold, with TNF and IL-1, respectively, and 8.2-fold with a combination of TNF and IL-1. Serum apo J concentrations were increased 2.3-fold by TNF, 79% by IL-1, and 2.9-fold with a combination of TNF and IL-1. These results demonstrate that apo J is a positive acute phase protein.